2016
DOI: 10.1089/jwh.2015.5242
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Pretest Probability and Exercise Treadmill Test in Korean Women with Suspected Coronary Artery Disease

Abstract: In Korean women, the observed prevalence of CAD was lower than the PTP, and PTP showed only marginal CAD predictability. Although a positive ETT independently predicted CAD, the ETT showed lower sensitivity and PPVs than previously reported. Despite the limited value of PTP and ETT, the high NPVs of ETT appear useful for saving patients from unnecessary further examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(33 reference statements)
2
2
0
Order By: Relevance
“…Therefore, statistics based on those studies are unlikely to provide a robust estimate for the CPX variables of interest in those study populations. The anthropometric features of our population sample fit within the reported standard ranges for East Asian populations, which suggests that the study sample reported herein is similar to normal/healthy adult populations across East Asian countries [8,15,[27][28][29][30].…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, statistics based on those studies are unlikely to provide a robust estimate for the CPX variables of interest in those study populations. The anthropometric features of our population sample fit within the reported standard ranges for East Asian populations, which suggests that the study sample reported herein is similar to normal/healthy adult populations across East Asian countries [8,15,[27][28][29][30].…”
Section: Discussionsupporting
confidence: 80%
“…Anthropometric features such as weight and height of the Caucasian and Asian population are different. For example, height, weight and BMI of subjects in an Asian population 14 16 19 20 21 22 23 were similar to those of the present study, but lower than those of primarily Caucasians. 12 13 18 As above, the predicted VO 2 max using Yaoshan equation using the Asian population had good agreement with our study.…”
Section: Discussionsupporting
confidence: 83%
“…In has been known that the prevalence of obstructive CAD was lower in Asian than in Western, especially in women. 24) 25) 26) Moreover compared to western women, Asian women presented more atypical symptoms in patients with stable angina. 27) Because clinical characteristics and risk factors of CAD were different between Asian and Western female patients, the accuracy of noninvasive diagnostic tests and its clinical applications need to be evaluated in Korean female patients.…”
Section: Discussionmentioning
confidence: 98%